Age and Gender Differences in Urea and Creatinine Levels among Diabetic Patients: A Retrospective Observational Study From a Tertiary Hospital in Yogyakarta, Indonesia - Yoni Astuti (CV. Inara, 2026)
Diabetes mellitus is a major global health problem associated with progressive renal complications, including diabetic nephropathy. Serum urea and creatinine are widely used biomarkers to assess renal function, yet their interpretation may be influenced by age and gender differences.This study aimed to analyze differences in urea and creatinine levels among diabetic patients based on age and gender and to evaluate their statistical significance.A retrospective observational study was conducted using medical record data from PKU Muhammadiyah Hospital, Yogyakarta, Indonesia, from Januari to December2025. Patients with complete data on age, gender, urea, and creatinine were included, while incomplete records were excluded. Subjects were stratified into three age groups: ≤50, 51–60, and ≥61 years. Independent sample t-tests were used to compare biomarker levels between males and females within each age group (p < 0.05 considered significant).Mean urea levels increased progressively with age in both genders. Male patients showed a consistent increase in both urea and creatinine levels across age groups, whereas females demonstrated less consistent creatinine trends. Significant gender differences were observed in the ≤50 years group for urea (p = 0.004) and creatinine (p = 0.042), while no significant differences were found in older groups. High variability in biomarker levels was observed, particularly among elderly patients.Age significantly influences urea levels in diabetic patients, while gender differences are more pronounced in younger individuals. These findings highlight the importance of age- and gender-specific interpretation of renal biomarkers in diabetes management.